![(\sqrt[5]{x^{7}})^{3}=(x^{\frac{7}{5}})^{3}=x^{\frac{7\cdot3}{5}}=x^{\frac{21}{5}}](https://tex.z-dn.net/?f=%28%5Csqrt%5B5%5D%7Bx%5E%7B7%7D%7D%29%5E%7B3%7D%3D%28x%5E%7B%5Cfrac%7B7%7D%7B5%7D%7D%29%5E%7B3%7D%3Dx%5E%7B%5Cfrac%7B7%5Ccdot3%7D%7B5%7D%7D%3Dx%5E%7B%5Cfrac%7B21%7D%7B5%7D%7D)
The root is equivalent to a fractional power with that number as the denominator. Otherwise, the rules of exponents apply.
5n + 7 = 7(n+1) - 2n
First distribute 7 to all terms inside the parenthesis
7(n) = 7n
7(1) = 7
5n + 7 = 7n - 2n + 7
Simplify. Combine like terms
5n + 7 = 5n + 7
True.
If you want to continue:
Isolate the n, move all variables to one side, and constants to the other
5n (-5n) + 7 (-7) = 5n (-5n) + 7 (-7)
0 = 0
True
hope this helps
When two variables have an inverse relationship, the slope is negatively correlated.
Answer:
-8
Step-by-step explanation:
-72 / 9 = -8
Answer:
side length= 4 mm
Step-by-step explanation:
The explanation is pretty easy;
You know that to get the volume of a cube the formula is length times width times height. You also know that all sides of a cube are equal. so what multiplied by itself 3 times = 64?
That would be 4; 4 times 4 = 16 then 16 times 4 = 64
<em>Sorry if the explanation wasn't great:(</em>